Prevalence and Factors Associated with Cervical Premalignant Lesions in Women 25-65 Years Attending ynaecology Clinic at Kampala International University Teaching Hospital - Richard Mulumba; Herman Lule; Collins Atuhaire; Ivan Bonet; Anaya Amnia Diaz (SAS Publishers, 2022)
The prevalence of cervical premalignant lesions and factors associated with progression into cervical cancer are poorly documented in Uganda. Knowledge of those at risk is mandatory to guide clinical practice and preventive policy formulation. In this Cross-sectional descriptive and analytical study of consecutively recruited participants, we determined the prevalence and factors associated with cervical premalignant lesions amongst women aged 25-65 years attending the gynecology clinic at Kampala International University Teaching Hospital, using investigator administered survey questionnaire between February 2017 and May 2017. We cystopathologically analyzed Pap smear samples obtained from study participants for positivity and grades of cervical premalignant lesions. We then conducted bivariate and multivariate analyses using STATA 14.0, to determine factors significantly associated with positivity and different grades of cervical premalignant lesions. Ethical clearance was obtained from Mbarara University of Science and Technology Research and Ethics Committee (IRB N0. 09/10-16).Of 315, cervical premalignant lesions were prevalent in 22% (n=69) with high grade squamous intra epithelial lesions (HSIL) comprising 13%. Those with history of tobacco smoking were twice more likely to test positive for cervical premalignant lesions (aPR 2.12; 95% CI [1.03-4.39]). Females who had ever screened before for cervical premalignant lesions were 1.7 times more likely to turn out positive compared to those who had never (aPR 1.71; 95%CI [1.01- 2.91]). Participants with presumed financial ability to pay for a pap test were 65% less likely to test positive for cervical premalignant lesions as compared to those who were financially not able to pay for pap test (aPR 0.35; 95% CI [0.15-0.83]. The prevalence of cervical premalignant lesions of 22% was higher compared to that reported in earlier studies. Tobacco smoking and prior history of screening were independent factors significantly associated with positivity for cervical premalignant lesions. Government and stakeholders should incorporate cessation of tobacco smoking campaigns into cervical cancer screening programs and prioritize the poor who cannot afford the Pap test.